Betawi Ethnic Parents' Perceptions of Girls' Higher Education - Made Saihu (RIRAI Publisher, 2022)
This paper concludes that parents of Betawi ethnicity in Tangerang city area have different perceptions about higher education for their daughters. Some of the differences in perception include: 1) Considering higher education very important, because women when they are married and have children, the mother becomes the